Investigation of the Impact of Electrochemical Hydrochlorination Process Parameters on the Efficiency of Noble (Au, Ag) and Base Metals Leaching from Computer Printed Circuit Boards - Serga, Vera; Zarkov, Aleksej; Shishkin, Andrei; Melnichuks, Maksims; Pankratov, Vladimir (MDPI, 2024)
The development of environmentally friendly and energy-saving processes for recycling electronic waste (e-waste) is still relevant today. The research presented in this work relates to hydrometallurgy, namely, the electrochemical leaching of metals from e-waste under the action of alternating current (AC) into hydrochloric acid solutions of electrolytes, and can be used for leaching both noble and non-ferrous metals from secondary raw materials. The main object of the study was disintegrator-crushed mixed computer PCBs metal-rich powders with a particle size (d) of <90 µm. The impact of such leaching process parameters as temperature (Tel) and composition of the electrolyte solution, AC density (i) on the electrodes, experiment duration (tex) while maintaining a constant electrolyte temperature (60 °C, 70 °C, and 80 °C) on the metal (Au, Ag, Cu, Al, Ni, Pb, Sn, Ti, Zn, and Fe) leaching efficiency has been studied. In addition, under similar experimental conditions, but without external control of Tel, the kinetics of metal leaching from raw material powders obtained via PCBs single and double crushing in a disintegrator has been also presented. Comparison of raw material powders obtained from different batches of the source material showed both the variability of its chemical composition and the different kinetics of Au and Ag leaching under the same experimental conditions. The optimal conditions for pretreatment of the raw material obtained by single crushing in a disintegrator (CHCl = 6 mol·L−1, i = 0.88 A·cm−2, tex = 1 h, solid-to-liquid ratio—8.6 g·L−1 and without external control of Tel) were determined. It has been shown that this electrochemical pretreatment is accompanied by transition of only base metals into the electrolyte solution, making it possible to significantly reduce their concentration in the final solution. Under pretreatment conditions, the following degree of metal leaching (RMe) has been established: RCu = 98.2%, RAl = 62.8%, RNi = 53.4%, RPb = 93.2%, RSn = 98.0%, RTi = 88.5%, RZn = 61.6%, and RFe = 78.8%. As a result of a subsequent two-hour electrochemical treatment of a solid residue, the degree of leaching of gold and silver was 73.6% and 86.7%, respectively. The presented results provide a broader understanding of the possibility of using the proposed electrochemical hydrochlorination method for noble and base metals leaching from waste PCBs. The novelty and practical value of this research is a validation of the developed technology in laboratory conditions using the real batch of the PCBs. This approach may also be useful to researchers involved in the recycling of other types of secondary raw materials. © 2024 by the authors. --//-- This is an open access article Serga V., Zarkov A., Shishkin A., Melnichuks M., Pankratov V.. Investigation of the Impact of Electrochemical Hydrochlorination Process Parameters on the Efficiency of Noble (Au, Ag) and Base Metals Leaching from Computer Printed Circuit Boards, (2024), Matals, 14 (1), art. no. 65; DOI: 10.3390/met14010065. Published under the CC BY 4.0 licence.
This research was supported by ERDF project no. 1.1.1.1/20/A/139 “Development of sustainable recycling technology of electronic scrap for precious and non-ferrous metals extraction”. The project was co-financed by REACT-EU funding to mitigate the effects of the pandemic crisis. The article was published with financial support from the Riga Technical University Research Support Fund. This research was also supported by the Institute of Solid State Physics, University of Latvia, as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; alternating current; base metals; electrochemical leaching; gold; mixed printed circuit boards; silver